Enhancing Animal Histology Through Eosin and Haematoxylin Staining Preparations - Lestari, Juniarti Wulan; Eunike Sri Puspaningsih; Made Karma Maha Wirajaya; Baiq Farista; Yuventi Nenometa (⁠International Journal of Sustainable Social Culture, Science Technology, Management, and Law Humanities, 2024)
Histology is a field of biology focused on examining tissue structure in detail using a microscope to analyse thinly sliced tissue samples. These sections reveal a variety of shapes, sizes, and layers, including cellular, fibrous, and tubular structures. Histology plays a crucial role in studying the normal tissue architecture of organs, addressing both anatomical and physiological aspects. This type of research employs a descriptive qualitative approach, utilizing secondary data primarily derived from literature such as journals and supporting articles. The literature review serves as an essential tool alongside contextual assessment, offering valuable insights and enhancing the understanding of the subject matter. Histological preparation involves the application of haematoxylin-eosin (HE) staining, which includes several key steps: tissue fixation, tissue selection (trimming), dehydration, clearing and tissue impregnation, tissue block creation, tissue sectioning, staining, and tissue examination.